Corruption as Cankerworms towards Economic Development in Nigeria - Suleiman, Ibrahim (American International Journal of Social Science Research, 2017)
Corruption has been corrosively eating the fabrics of the Nigerian nation. Its persistence in the form of fraud, mismanagement, misappropriation, diversion of public funds, tax evasion, money laundering etc. has led Nigeria into unfortunate national and even international circle of criminal minded persons. This therefore has made the development of the country and its attendant benefits only a paper work or rather an illusion. This paper conceptualizes corruption beyond the point of public officers taking bribes and gratification, committing fraud, stealing public funds and assets to equally include, deliberate violation of standards for gainful ends which may be in cash or kind. It therefore, encompasses any decision, act or conduct that is considered pervasive to democratic norms and values. The method utilized by this work is incidence analysis and documentary research. The paper which is divided into five sections concluded that, only anti-corruption policies and programs anchored on ethical, balanced, independent, and self-sustained, people oriented can succeed in Nigeria and thereby ensure national economic development. The paper recommended among other things for a successful anti-corruption crusade in third world countries that, international agencies such as Paris Club, IMF, World Bank, UNO should review their policies and conditions to reflect war against corruption especially among third World leaders even while in office. That a mandatory involvement of all community based organizations be considered in annual budget formulation, monitoring and evaluation to avoids misappropriation and looting in the country.